Quantitative Analysis of Nanorough Hydrogenated Si(111) Surfaces through Vibrational Spectral Assignment by Periodic DFT Calculations - Holovský, Jakub; Šebera, Jakub; Sychrovský, Vladimír; Zemen, Jan; De Wolf, Stefaan; Ballif, Christophe (Journal of physical chemistry. C, 2022)
In this work, we use periodic density functional theory (periodic DFT) to rigorously assign vibrational spectra measured on nanorough wet-processed hydrogenated Si(111) surfaces. We compare Si(111)-(1 × 1) surfaces etched by dilute HF and NH4F, featuring two vibrational patterns that systematically appear together. They are attributed to vibrations observed on vicinal surfaces featuring 112̅ and 1̅1̅2 steps terminated with monohydrides and dihydrides, respectively. For the first time, we fully assign vibration patterns of realistic silicon surfaces with variable nanoroughness directly by periodic DFT simulations involving contributions from isolated species but also contributions from highly coupled species forming standing waves. This work opens the path to a better quantitative characterization of imperfect and nanorough Si(111) surfaces from vibrational spectra.